2013
DOI: 10.1016/j.sbspro.2013.08.920
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Intrapreneurship: In A Service Sector in Turkey

Abstract: The purpose of this study is to comprehend the statistical relation between the amount of turnover produced by an employee in insurance companies in Turkey, used as a dependent variable. Whereas, the independent variables are three.The first independent variable is the ratio of number of staff horldiong a Bachelor (BA) over the number of all employees of each insurance company. The second independent varaible is the ratio of the number of sales department crew over number of all employees of each insurance com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 3 publications
2
18
0
3
Order By: Relevance
“…Evidently, when intrapreneurial engagement goes up by 1, organisational survival goes up by 0.837. These findings validate the submissions of Irawanto (2015) and Serinkan, Kaymakci, Arat & Avcik (2013). This suggest that when employees are given autonomy to develop worthwhile intrapreneurship innovation with appropriate competitive reward system, it will motivate employees to think and behave like intrapreneurs and as well be committed to chart the course since they are involved in the process.…”
Section: Results and Discussion Of Findingssupporting
confidence: 79%
See 1 more Smart Citation
“…Evidently, when intrapreneurial engagement goes up by 1, organisational survival goes up by 0.837. These findings validate the submissions of Irawanto (2015) and Serinkan, Kaymakci, Arat & Avcik (2013). This suggest that when employees are given autonomy to develop worthwhile intrapreneurship innovation with appropriate competitive reward system, it will motivate employees to think and behave like intrapreneurs and as well be committed to chart the course since they are involved in the process.…”
Section: Results and Discussion Of Findingssupporting
confidence: 79%
“…The implication of this to the management is that, if conducive working environment that allows employees to think outside the box is provided and efforts are being rewarded, there is every likelihood that employees will turn opportunities at their disposal into new innovations that will enhance organisational sustainability. This validates the submission of Serinkan et al (2013) that if employees are given opportunities to explore and management provides good working environment, it will trigger intrapreneurial initiatives. Another managerial implication is that if employees are empowered and are given autonomy, it will encourage them to think of new business opportunities and innovate to take advantage of the opportunities around them.…”
Section: Discussionsupporting
confidence: 68%
“…Entrepreneurial intention and organisational commitment Luca and Simo (2016) in a scholarly article found that organisations impose common aims, objectives, rules, chains of command and control to their employees that drastically limit individual initiative and autonomy. Serinkan et al (2013) indicated that, even in large organisations, entrepreneurial behaviour in employees is seen as favourable to increase the competitiveness and performance of the employees. Gbadamosi and Nwosu (2011a, b) articulated that entrepreneurial intention and job satisfaction are the significant predictors of organisational commitment.…”
Section: Entrepreneurial Intention and Job Satisfactionmentioning
confidence: 99%
“…Penelitian dari Gbadamosi dan Nwosu (2011); Luca dan Simo (2016); dan Serinkan et al (2013) menyatakan bahwa komitmen organisasi berpengaruh terhadap intensi berwirausaha karyawan. Dengan demikian hipotesis penelitian ketiga dinyatakan bahwa komitmen organisasi berpengaruh positif signifikan terhadap intensi berwirausaha karyawan.…”
Section: Rerangka Konseptual Dan Hipotesi Penelitianunclassified
“…Hasil penelitian berdasarkan pembuktian hipotesis ketiga menunjukkan bahwa komitmen organisasi berpengaruh positif signifikan terhadap intensi berwirausaha (Gbadamosi dan Nwosu, 2011;Luca dan Simo, 2016;Serinkan et al, 2013). Hal ini menunjukkan bahwa karyawan akan bersedia berkomitmen dengan organisasi apabila mereka merasa puas dengan pekerjaannya.…”
unclassified